Modulation of the carrier balance of lead-halide perovskite nanocrystals by polyelectrolyte hole transport layers for near-infrared light-emitting diodes. Issue 9 (September 2022) - Lee, Chih-Chien; Iskandar, Johan; Kurniawan, Ade; Hsu, Hung-Pin; Wu, Ya-Fen; Cheng, Hsin-Ming; Liu, Shun-Wei
Abstract: An alternative material, methylamine (MA)-doped poly[3-(4-carboxymethyl)thiophene-2, 5-diyl] (P3CT) as hole transport layer (HTL) was investigated for efficient solution-processed near-infrared perovskite light-emitting diodes (NIR PeLEDs). The best NIR PeLEDs performance was achieved with an optimized composition ratio of the MA-doped P3CT (1:1) due to the balance of the electron and hole carrier in the active layer. The charge-balanced NIR PeLEDs exhibit the highest radiance of 858.37 W sr −1 m −2, a low turn-on voltage of 1.82 V, and an external quantum efficiency of 7.44%. Our findings show that using P3CT as an alternative HTL has the potential to significantly improve PeLED performance, allowing it to play a role in the development of practical applications in high-power NIR LEDs. Abstract : NIR PeLEDs; Hole transport layer; P3CT, Charge balance.